PtoMYB170 positively regulates lignin deposition during wood formation in poplar and confers drought tolerance in transgenic Arabidopsis. (28th July 2017) - Xu, Changzheng; Fu, Xiaokang; Liu, Rui; Guo, Li; Ran, Lingyu; Li, Chaofeng; Tian, Qiaoyan; Jiao, Bo; Wang, Bangjun; Luo, Keming
Abstract: Wood formation is a complex developmental process under multi-level transcriptional control executed by a large set of transcription factors. However, only limited members have been characterized to be key regulators of lignin biosynthesis in poplar. Here we report the conserved and unique functions of PtoMYB170, a transcription factor identified from Populus tomentosa (Chinese white poplar), in lignin deposition and drought tolerance in comparison with its duplicate paralog PtoMYB216. PtoMYB170 is preferentially expressed in young leaves and xylem tissues. Overexpression of PtoMYB170 in transgenic poplar plants resulted in stronger lignification and more thickened secondary wall in xylem compared with wild-type plants, whereas the CRISPR/Cas9-generated mutation of PtoMYB170 weakened lignin deposition, thereby leading to a more flexible and collapsed xylem phenotype. Transient expression experiments demonstrated that PtoMYB170 specifically activated the expression of lignin biosynthetic genes, consistent with the function of PtoMYB216. However, GUS staining assays revealed that PtoMYB170 was specifically expressed in guard cells of transgenic Arabidopsis while PtoMYB216 was not. Heterologous expression of PtoMYB170 in Arabidopsis enhanced stomatal closure in the dark and resulted in drought tolerance of the transgenic plants through reduced water loss, indicating a diversified role from PtoMYB216 . These results revealed the PtoMYB170 -dependent positive transcriptional regulation on lignin deposition in poplar and its coordinated function in enhancing drought tolerance by promoting dark-induced stomatal closure.